Conceptualization of Pragmatic Language Through Proverbs: A Comparative Study of Arabic and English Proverbs (المجلة الدولية للعلوم التربوية والآداب, 2024)
This study aims to analyze and compare several proverbs in Arabic and English from a linguistic-pragmatic perspective. Examining the similarities and differences of proverbs in different languages helps us appreciate the use of that language. Indeed, Arabic and English may constitute an excellent example of understanding the practical use of common proverbs and, more generally, the historical facets of these languages' background. In doing so, I identified twenty common sayings used in the two languages, Arabic and English, to investigate the parallelisms among them and observe their use in a particular cultural context. The study's originality focuses on the fact that until now, proverb cross-language studies on these languages from a metalinguistic point of view have not been examined.